Extension and validation of a revised Cassie-Baxter model for tailor-made surface topography design and controlled wettability. (5th May 2021) - Lempesis, Nikolaos; Koopmans, Rudolf J; Díez-Ahedo, Ruth; Kristiansen, Per Magnus
Abstract: Predicting wettability accurately across various materials, surface topographies and wetting liquids is undeniably of paramount importance as it sets the foundations for technological developments related to improved life quality, energy saving and economization of resources, thereby reducing the environmental impact for recycling and reuse. In this work, we extend and validate our recently published wetting model, constituting a refinement of the original Cassie-Baxter model after consideration of realistic curved liquid-air interfaces. Our model enabled more meaningful contact angle predictions, while it captured the experimentally observed trends between contact angle and surface roughness. Here, the formalism of our wetting model is further extended to 3D surface topographies, whereas the validity of our model, in its entirety, is evaluated. To this end, a total of thirty-two experimentally engineered surfaces of various materials exhibiting single- and multilevel hierarchical topographies of increasing complexity were utilized. Our model predictions were consistently in remarkable agreement with experimental data (deviations of 3%–6%) and, in most cases, within statistical inaccuracies of the experimental measurements. Direct comparison between experiments and modeling results corroborated that surface topographies featuring re-entrant geometries promoted enhanced liquid-repellency, whereas hierarchical multilevel surface topographies enabled even more pronounced nonwetting behaviors. For the sinusoidal topography, consideration of a second superimposing topography level almost doubled the observed water contact angles, whereas addition of a third level brought about an extra 12.5% increase in water contact angle.